Melindungi Hak Pekerja Di Era Normal Baru - Prilly Priscilia Sahetapy; Fajar Sugianto; Tomy Michael (ADALAH, 2020)
AbstractThe law plays an active role in providing a sense of security for everyone in all situations, including the situation the world is experiencing in the last few months. The Corona pandemic caused multidimensional shocks, such as in the education, health and economic sectors. Compared to other sectors, it is the economic sector that has the most attention. The Central Statistics Agency noted that the rate of economic growth in Indonesia experienced a slowdown which fell in the first quarter of 2020, which was only 2.97%. Meanwhile, economic growth in the first quarter of 2019 was at 5.07%. The impact of the corona pandemic in the economic sector also has an impact on the labor sector. The Indonesian government has implemented a policy to work from home (WFH) since mid-March 2020. However, not all work can be done from home so that many workers still have to experience layoffs. The government should make regulations at the level of laws in order to better protect workers. This is important so that workers can still make ends meet in difficult times like thisKeywords: force majeure; laborer; right AbstrakHukum berperan aktif untuk memberikan rasa aman bagi setiap orang dalam segala situasi, termasuk situasi yang tengah dialami dunia beberapa bulan terakhir ini. Pandemi Corona menimbulkan guncangan multidimensi, seperti dalam sektor pendidikan, kesehatan, dan ekonomi. Dibandingkan dengan sektor-sektor yang lain, sektor ekonomi yang paling banyak disoroti. Badan Pusat Statistik mencatat bahwa laju pertumbuhan ekonomi di Indonesia mengalami perlambatan yang jatuh di Kuartal I/2020, yaitu hanya 2,97%. Sementara itu, pertumbuhan ekonomi pada Kuartal I/2019 berada di angka 5,07%. Dampak pandemi corona dalam bidang ekonomi turut berimbas pada bidang ketenagakerjaan. Pemerintah Indonesia memberlakukan kebijakan untuk bekerja dari rumah atau Work From Home (WFH) sejak pertengahan Maret 2020. Akan tetapi, tidak semua pekerjaan dapat dilakukan dari rumah sehingga banyak tenaga kerja yang masih harus mengalami PHK. Pemerintah seharusnya membuat peraturan setingkat undang-undang agar dapat lebih melindungi pekerja. Hal ini menjadi penting agar para pekerja tetap dapat memenuhi kebutuhan hidup di masa-masa sulit seperti iniKata kunci: hak; force majeure; pekerja